2002
DOI: 10.4049/jimmunol.169.2.1126
|View full text |Cite
|
Sign up to set email alerts
|

Histone Peptide-Induced Nasal Tolerance: Suppression of Murine Lupus

Abstract: Induced mucosal tolerance has been shown to be beneficial in preventing or treating a number of murine and human autoimmune disorders. However, this particular form of therapy has not been thoroughly tested in systemic lupus erythematosus. In this study, we investigated the conditions for induction of nasal tolerance using a histone peptide named H471 expressing a dominant T cell epitope in the histone protein H4 of mononucleosome in lupus-prone SNF1 female mice. We also tested the effect of chronic peptide na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 39 publications
2
48
0
1
Order By: Relevance
“…However, evidence supporting our hypothesis comes from the finding that expression of CD80 on APCs of SLE patients is intrinsically defective [33]. It has been previously reported that induction of nasal tolerance in lupus prone SNF1 mice resulted in the suppression of T-cell proliferative response, autoantibody production and disease progression [15]. In the second part of this study we examined the role of B cells in the induction of nasal tolerance and the mechanism of tolerance in NZB mice.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, evidence supporting our hypothesis comes from the finding that expression of CD80 on APCs of SLE patients is intrinsically defective [33]. It has been previously reported that induction of nasal tolerance in lupus prone SNF1 mice resulted in the suppression of T-cell proliferative response, autoantibody production and disease progression [15]. In the second part of this study we examined the role of B cells in the induction of nasal tolerance and the mechanism of tolerance in NZB mice.…”
Section: Discussionmentioning
confidence: 77%
“…Mice were nasally dosed for 5 consecutive days with 0.4 mg/day of H471 dissolved in PBS (BioWhittaker, MD, USA) or PBS alone [15]. For antigen priming, each mouse received 100 mg of peptide antigen emulsified in CFA (Sigmae Aldrich, MO, USA) intradermally.…”
Section: Tolerance Induction and Immunization Protocolmentioning
confidence: 99%
“…Like highdose tolerance i.v. (8), nasal tolerance with one of the autoepitopes, H4 71-94 , also could delay or treat lupus nephritis in SNF1 mice, but by generating IL-10-producing T cells (39). IL-10-producing T reg cells might benefit lupus with some caveats (30,40).…”
Section: Discussionmentioning
confidence: 99%
“…We were initially surprised that CD4 ϩ T cells from tolerant mice failed to produce IL-10, particularly in the light of previous reports, using autoimmune models, demonstrating a role for IL-10 in tolerance induction. [38][39][40][41] However, the finding that IL-10 Ϫ/Ϫ mice can be made tolerant by intranasal administration of peptide ( Figure 1E) as well as wild-type mice ( Figure 1A) clearly shows that in this transplantation model, IL-10 does not play a crucial role. Our observations of a limited capacity for cytokine production by antigen-specific cells from tolerant mice are more consistent with the findings of a recent report, 42 showing that although the ability of transgenic CD8 ϩ cells to proliferate in response to antigen is indistinguishable whether the cells are transferred into naive or tolerant recipients, cytokine production and the cytotoxic capacity of transgenic cells transferred into tolerant hosts are impaired.…”
mentioning
confidence: 92%